2004
DOI: 10.1158/0008-5472.can-04-0328
|View full text |Cite
|
Sign up to set email alerts
|

Array Comparative Genomic Hybridization Analysis of Colorectal Cancer Cell Lines and Primary Carcinomas

Abstract: Array comparative genomic hybridization, with a genome-wide resolution of ϳ1 Mb, has been used to investigate copy number changes in 48 colorectal cancer (CRC) cell lines and 37 primary CRCs. The samples were divided for analysis according to the type of genomic instability that they exhibit, microsatellite instability (MSI) or chromosomal instability (CIN). Consistent copy number changes were identified, including gain of chromosomes 20, 13, and 8q and smaller regions of amplification such as chromosome 17q11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
142
3
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(167 citation statements)
references
References 54 publications
21
142
3
1
Order By: Relevance
“…31 Although a few studies have reported on losses of the short arm of chr16 in CRC, this has not received much attention. 12,[32][33][34][35] Our analyses indicate that the genomic rearrangement leading to chr16p-loss is an early event occurring in $ 30% of adenomas. The frequency is even higher in carcinomas (>50%), independently of MSS and MSI status, indicating that the causing mechanism is independent of the DNA mismatch repair system.…”
Section: Discussionmentioning
confidence: 72%
“…31 Although a few studies have reported on losses of the short arm of chr16 in CRC, this has not received much attention. 12,[32][33][34][35] Our analyses indicate that the genomic rearrangement leading to chr16p-loss is an early event occurring in $ 30% of adenomas. The frequency is even higher in carcinomas (>50%), independently of MSS and MSI status, indicating that the causing mechanism is independent of the DNA mismatch repair system.…”
Section: Discussionmentioning
confidence: 72%
“…Davidson et al, 2000;AbdelRahman et al, 2001;Karan et al, 2003;Hurst et al, 2004;Hwang et al, 2004), and more recently array CGH has begun to provide more detail of these losses (e.g. Paris et al, 2003;Douglas et al, 2004;Hurst et al, 2004;Nakao et al, 2004;Garcia et al, 2005). Distal 8p also frequently shows loss of heterozygosity (LOH), which would often reflect loss through unbalanced translocation (for references see Adams et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…23,24 These changes include amplifications on chromosome 20q, 13 and 8q, and copy number loss on the long arm of chromosome 18 and on chromosome 8p. [24][25][26][27][28] Both aberrant specimens showed amplifications of entire chromosomes: 7, 13 and 16, as well as partially overlapping aberrations on chromosome 20 (Figure 4a). …”
Section: Validation For Downstream High-throughput Technologiesmentioning
confidence: 99%